Demographic and clinical aspects of an Italian patient population with chronic fatigue syndrome - N. Carlo-Stella; M. Cuccia (PAGEPress Publications, 2011)
Chronic Fatigue Syndrome (CFS) is a debilitating syndrome characterized by fatigue which, by exclusion, cannot be ascribed to another illness. Because of the vagueness of the symptoms and signs in patients with CFS, various attempts have been made to define the syndrome and classification criteria have been developed (1- 3), of which the most well-known and used are those of Fukuda et al. (1) This classification includes two major criteria...